Um debate emancipatório em saúde mental: uma análise da histeria em Don’t look up - Camila Fortes Monte Franklin (e-cadernos ces)
This paper aims to analyze the meanings attributed to female hysteria associated with the character Kate Dibiasky in the 2021 film Don’t look up. Offering possible materiality to engage more fully an emancipatory debate on mental health, the film offers a critique of power relations and gender stereotypes, especially in a context of scientific denialism. Using Narratology as a theoretical-methodological guide, the research seeks to point out the critical nuances that reinforce the profile of female hysteria through a satirical plot set in an ‘end of the world’ scenario. Although the film is not built on a debate aimed at mental health, an analysis of the film points to the existence of a dissident narrative about hysteria, becoming an invitation to rethink hegemonic psychiatric models in addition to broadening therapeutic validity.